Clinical, cognitive and biomarker profiles in dominantly‐inherited versus sporadic early‐onset Alzheimer's disease. (31st December 2021) - Llibre‐Guerra, Jorge J; Iaccarino, Leonardo; Li, Yan; Edwards, Lauren; McDade, Eric; Strom, Amelia; Gordon, Brian A.; Mundada, Nidhi; Schindler, Suzanne E.; Tsoy, Elena; Fagan, Anne M; La Joie, Renaud; et al.
Abstract: Background: Approximately 5% of Alzheimer disease (AD) occurs before the age of 65, known as early onset AD (EOAD); 5‐10% of the patients with EOAD are caused by dominantly inherited mutations (DIAD) and the remainder appear to be sporadic EOAD (sEOAD). The extent to which clinical presentations, cognitive and biomarker profiles in DIAD and sEOAD overlap remains unknown. Methods: We compared the clinical presentation, cognitive performance and cerebrospinal fluid (CSF) AD biomarker concentrations in DIAD and sEOAD. We included all DIAD symptomatic (CDR>0) participants (n=92) from the Dominantly Inherited Alzheimer Network (DIAN) cohort and 120 sEAOD symptomatic participants from the UCSF Alzheimer's Disease Research Center. All EOAD cases were amyloid‐positive via PIB‐PET. All participants completed clinical measures, a battery of cognitive tests and CSF biomarker studies (Aβ‐42, p‐tau‐181, t‐tau). Baseline differences in clinical and biomarkers variables between sEOAD and DIAD were compared using t ‐tests, and differences in the rates of decline on clinical and cognitive measures were compared using linear mixed effects models. Results: DIAD participants had an earlier age at symptom onset compared to the sEOAD group (42.9y (±8.1) and 54.8y (±5.1) respectively, p<0.001). The sEOAD group showed a lower performance on executive measures, including verbal fluency (p=0.001), Trail making test (p=0.001) and digit span (p<0.001). CSF Aβ‐42 levels were significantly lower in DIAD compared to sEOAD participants (242.0 pg/ml [IQR=164.5, 318.8] vs 295.0 pg/ml [IQR=243.9, 364.1] respectively, p=0.014). Ptau‐181 levels were higher in the DIAD cohort (p=0.003), but no significant differences were found for t‐tau levels (p=0.11). Longitudinal analyses did not reveal significant differences in the rates of functional (CDR TM ‐SB) and cognitive (MMSE) decline between two groups. Conclusions: Although sporadic and inherited EOAD differed in AD core pathological CSF biomarkers concentrations and baseline cognitive profiles, the rates of functional and cognitive changes were similar across these groups. These findings provide unique insights into the similarities and differences between DIAD and sEOAD and may inform the design of future clinical trials.